Trends in augmented reality tracking, interaction and display: A review of ten years of ISMAR - Feng Zhou; Duh, Henry Been-Lirn; Billinghurst, Mark (2008 7th IEEE International Symposium on Mixed and Augmented Reality, 2008)
Although Augmented Reality technology was first developed over forty years ago, there has been little survey work giving an overview of recent research in the field. This paper reviews the ten-year development of the work presented at the ISMAR conference and its predecessors with a particular focus on tracking, interaction and display research. It provides a roadmap for future augmented reality research which will be of great value to this relatively young field, and also for helping researchers decide which topics should be explored when they are beginning their own studies in the area.